Determinants Of Inflation In Algeria During The Period Of 1970-2022, An Empirical Study Using The Ardl Model - Mekkaoui Mohammed (جامعة الوادي University Of Eloued, 2024)
This study aims to identify the most important economic variables determining inflation in Algeria during the of period 1970-2022, and to achieve this, the concept, types and the most important theories explaining inflation were addressed at the beginning, then an econometric study was carried out to equate the determinants of inflation based on the autoregressive distributed time lag model ARDL. The results of the study revealed the existence of a long-term relationship between inflation and GDP, imports and the exchange rate. The study also found that the exchange rate is a basic determinant of inflation in the short and long terms for the Algerian economy during the study period.
Keywords: Inflation; Determinants of inflation; Algeria; ARDL